Racial/ethnic differences in necrotizing enterocolitis incidence and outcomes in premature very low birth weight infants. (October 2018) - Jammeh, Momodou; Adibe, Obinna; Tracy, Elisabeth; Rice, Henry; Clark, Reese; Smith, P.; Greenberg, Rachel
Abstract Background As advances in neonatal intensive care increase the survival of extremely premature infants, the at-risk population for necrotizing enterocolitis (NEC) continues to rise. Although racial health disparities in preterm births have been well documented, large-scale studies exploring racial differences in NEC outcomes are lacking. Here, we conduct a study of racial health disparities in NEC using a nationally representative multicenter cohort. Study design Infants ≤1500 g birth weight and ≤30 weeks gestational age admitted in the first week after birth to neonatal intensive care units in the Pediatrix Medical group from 1997 to 2015 were included. Multivariable logistic regression was used to determine the adjusted odds ratio (AOR) of risk factors related to NEC and associated mortality. Results Of the 126, 089 (45% non-Hispanic White, 27% non-Hispanic Black, and 19% Hispanic) infants who met the inclusion criteria, 8796 (7%) developed NEC. On multivariable analysis, non-Hispanic Black and Hispanic infants had higher odds of developing NEC (AOR 1.31, 95% confidence interval (CI) [1.24–1.39], p < 0.001 and AOR 1.30 [1.21–1.39], p < 0.001, respectively). Among infants with NEC, mortality was higher in non-Hispanic Black and Hispanic infants compared to non-Hispanic White infants (AOR 1.35 [1.15–1.58], p < 0.001 and AOR 1.31 [1.09–1.56], p = 0.003, respectively). Conclusion Our study demonstrates that non-Hispanic Black and Hispanic infants are significantly more likely to be diagnosed with NEC. In addition, non-Hispanic Black and Hispanic infants have higher odds of death after NEC compared to non-Hispanic White infants. Further studies are necessary to investigate the etiology of these health disparities and to test interventions to improve these health outcomes.